Clinical characteristics of Chinese neonates with neonatal-onset multisystem inflammatory disease: a case report and literature review - Zhao, Cui; Liu, Chen; Li, Xiaoying (Frontiers in Immunology, 2024)
Background: Neonatal-onset multisystem inflammatory disease (NOMID) is a rare and severe autoinflammatory disease caused by mutations of the NLRP3 gene and is characterized by a skin rash, fever, arthropathy, and neurologic manifestations. We herein report a neonatal case with recurrent rash, fever, and meningitis from 12 h after birth, and NOMID was diagnosed during the neonatal period. We also reviewed the clinical characteristics and genetic mutations of previously reported Chinese neonates with NOMID.Case presentation and literature review: NOMID is rare in China, and there have been over 100 cases uncovered thus far, including ours. The patient we reported here was the youngest among the confirmed Chinese cases and had the de novo mutation c.1210G>C (p.V404L) in exon 4 of the NLRP3 gene, which has not been reported previously. All 25 patients manifested recurrent urticaria-like rash, and 24 were febrile.Of the 23 patients with genetic data available, all had NLRP3 mutations. The primary treatment of these patients entailed glucocorticoids and immunosuppressants; however, the IL-1 inhibitor was rarely used due to its current unavailability in China. One patient was cured by umbilical cord blood stem cell transplantation (UCBT), which provided an alternative treatment.We recommend that NOMID be considered for neonates with recurrent rash, fever, and aseptic meningitis. However, further research on underlying mechanisms and therapeutic regimens in China is necessary to provide improved management.